Highly robust crystalsome via directed polymer crystallization at curved liquid/liquid interface - Wenda Wang (Nature Portfolio, 2016)
Self-assemblies of polymers to form polymersomes in solution can be used as carriers for drug delivery, but it is challenging to control polymer crystallization to improve their mechanical stability. Here, Wang et al.show the formation of nanosized crystalsomes composed of polymer lamellar single crystals.